Facies analysis of the Semanggol Formation, South Kedah, Malaysia: A possible PermianâTriassic boundary section - Baioumy, H. (Springer Verlag, 2016)
Although the PermianâTriassic Semanggol Formation is widely distributed in northwestern Peninsula Malaysia and is made of various lithofacies, its sedimentology and possible relation with the PermianâTriassic boundary (PTB) were not considered before. In this study, detailed facies analysis was conducted for two sections of the Semanggol Formation at the Bukit Kukus and Baling areas, South Kedah to clarify its sedimentology and relation to the PTB. Four facies from the Permian part of the Semanggol Formation that were identified at the Bukit Kukus section include laminated black mudstone, interbedded mudstone and sandstone, volcanogenic sediments, and bedded chert. In Baling area, the Triassic part of the formation is classified into three members. The lower member comprises of claystone and bedded chert facies, while the middle member is composed of sandstone and claystone interbeds (rhythmite). On the other hand, the upper member is grouped into two main units. The lower unit is mainly claystone and includes two facies: the varve-like laminated silt and clay and massive black claystone. The upper unit is composed of various sandstone lithofacies ranging from hummocky cross stratified (HCS) sandstone to thinly laminated sandstone to burrowed sandstone facies. The HCS sandstones occur as two units of fine-grained poorly sorted sandstone with clay lenses as flaser structure and are separated by a hard iron crust. They also show coarse grains of lag deposits at their bases. The laminated black mudstone at the lowermost part of the Semanggol Formation represents a reducing and quite conditions, which is most probably below the fairweather wave base in offshore environment that changed upwards into a fining upward sequence of tide environment. Abundance of chert beds in the volcanogenic sediments suggests the deposition of tuffs and volcanic ashes in deep marine setting which continues to form the Permian pelagic bedded chert and claystone. The bedded chert in the lower member of the Triassic section suggests its formation in deep marine conditions. The rhythmic sandstone and claystone interbeds of the middle member are suggestive for its formation as a distal fan of a turbidite sequence. Lithology and primary sedimentary structure of the upper member suggest its deposition in environments range from deep marine represented by the varve-like laminated silt and clay to subtidal environment corresponds to the massive black claystone to coastal environment represented by the hummocky sandstone units and reaches the maximum regression at the hiatus surface. Another cycle of transgression can be indicated from the second hummocky unit with transgressive lag deposits that develops to relatively deeper conditions as indicated from the formation of relatively thick laminated sandstone and bioturbated massive sandstone facies that represent tidal and subtidal environment, respectively. Late Permian lithological variation from the radiolarian chert into early Triassic claystone probably resulted from a decrease in productivity of radiolarians and might represent a PTB in the Semanggol Formation. Volcanogenic sediments in the studied section can be used as an evidence for volcanic activities at the end of the Permian, which is probably connected to the nearby volcanic ash layers in the eastern China, the ultimate cause of the PTB in this area. Black mudstone in the Permian part of the studied section may be interrelated to the Latest Permian Anoxia that started to build in the deep ocean well before the event on shallow shelves. Â© 2016, Saudi Society for Geosciences.